Processos erosivos avançados em São Francisco de Assis RS: estudo de caso - Corrêa, Lourenço da Silveira Lima (2006)
The present paper analyses the erosive processes that have been developed in São Francisco de Assis county, between the peripheric depression and the Rio Grandense plateau. The studied area is located between the 55° 18'46"w and 55°16'00"w, 29°34'50"s and 29°32'55"s elose to, the new road RST 377. The study considers the drainage headcuts of a small hydrological basin connected to Ibicuí River, related to others in the neighborhood. The area is 357,72ha and the perimeter is 7929m. The purpose of this paper is to describe the gully and others erosive processes in different degrees of development, the factors that interfere in the origin and de evolution of the erosive processes in the region; to offer alternatives to stop the degradation of the erosive processes and the possible rehabilitation of the degraded areas, observing a restricted area. The identificated were elassified and maps were made. The erosive landforms have been studied by geomorphology alteration of the earth surface. l1's important to establish systems to observe the evolution of the erosive processes in arder to plan actions to preserve the productive areas and to stop the degradation of the environment in those areas and the around areas because processes like those are increasing in the whole region.